Analisis Penerapan PPH Final Berdasarkan PP 23 Tahun 2018 Pada PT. XYZ - Sandra Tanuwijaya, Purnamawati Helen Widjaja, Henny (Fakultas Ekonomi, Universitas Tarumanagara, 2022)
This research aims to identify the impact of the application of PP No. 23 Year 2018 on income tax payable that should be paid by PT. XYZ in 2019. Further, this study will also compare income tax calculated on the basis of PP No. 23 Year 2018 to the calculation of income tax on the basis of bookkeeping method under Law No. 36 Year 2008. Data are obtained through interview with PT. XYZ and data documentation provided by PT. XYZ in the form of 2019 income statement of PT. XYZ. The data processing method relied upon descriptive analysis method. The result of this study indicates that the use of taxation obligation calculation method on the basis of PP No. 23 Year 2018 may affect the amount of tax expense and thus, may also affect the net income earned by PT. XYZ in the current year. The implication of this study is PT. XYZ needs to consider the income tax calculation method to be used by taking into account gross income, cost of goods sold, and expenses that may affect its income statement in order for PT. XYZ to receive maximum profit in the current year.